Biocomposites reinforced with natural fibers:thermal, morphological and mechanical characterization - Lemos,Alessandra Luiza de (2017)
ABSTRACT This study evaluates the thermal, morphological and mechanical behavior of polypropylene (PP) composite with different natural fibers. The fibers used were wood, sugarcane, bamboo, babassu, coconut and kenaf with and without coupling agent. The thermal, morphological and mechanical properties were evaluated, and a composite PP+GFPP (glass fiber) was used as reference. The interaction at the interface fiber-polymer matrix was studied by scanning electron microscopy (SEM) at the fractured surface of the composites, as expected the presence of maleic anhydride (MA) as coupling agent increasedthe interaction at the interface. The influence of natural fiber in the degree of crystallinity of the composites was evaluated by DSC analysis. The samples of PP+GFPP and PP+(PP-MA)+WF (wood flour) showed better temperature stability. PP+GF also presented superior flexural modulus. The thermal dynamic mechanical behavior was evaluated by DMA, a decrease in storage modulus with increasing temperature was observed, the PP+GF and the composite containing maleic anhydride and sugarcane fiber showed higher modulus. The natural fiber biocomposites studied, consistently presented lower flexural modulus and tensile strength than the reference composite, with and without the use of coupling agent. As expected the use of natural fibers lowered the density compared to the reference material.